Оптимизация распределения температуры в ростовом объеме аппарата высокого давления типа «тороид» - Шевчук, С.Н.; Гаран, А.Н.; Ивахненко, С.А.; Заневский, О.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Settlement methods define increase possibility growth volume of cells for single diamond crystals growing in toroid type high pressure equipment. It is shown that at volume increase of the growth cell on 25 % limiting values of temperature in characteristic points do not exceed the maximum values for this type equipment. It is shown that at growing of the big size samples the temperature distribution in growth volume corresponds to requirements for growing of structurally perfect single diamond crystals.